Pemanfataan Limbah Kain Perca menjadi Dotapouch (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Cloth scraps are considered waste that has no value, whereas this waste can be utilized so that it has economic value. The utilization of cloth scraps is expected to help SKOPER mothers and PKK mothers develop innovations and creativity. The method used in implementing this community service activity is the Asset Based Community Development (ABCD) method. This method has five steps, namely: 1) Discovery (Assessment), 2) Dream (Dream), 3) Design (Design), 4) Define (Determine goals), and 5) Destiny (Do). The result is that the manufacture of this dotapouch product has several benefits and functions, and has a positive impact in terms of social and economic.